Physical activity and absenteeism for worker’s disease: a systematic review - Viana, Michell Vetoraci; Ferraz, Almir de França; Figueiredo, Tiago Costa de; Rica, Roberta Luksevicius; Salaroli, Luciane Bresciani; Bocalini, Danilo Sales; Miranda, Maria Luiza de Jesus; Júnior, Aylton Figueira (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Introduction: Although Brazil has complete legislation that establishes guidelines and recommendations for companies regarding Occupational Health and Safety, according to data from the Ministry of Labor and Social Security, indices of absenteeism and absences from work functions increase with each year. Objective: To identify the association of the level of physical activity on absenteeism by diseases in workers, through a systematic review. Methods: Four databases (Lilacs, SciELO, Medline via Pubmed and Cochrane Library) were consulted from November 10 to 23, 2017. Results: The selection process of the articles were included after screening 25 articles: (08) articles did not mention workers, only school children, (05) articles were systematically reviewed, and (12) articles had randomized clinical trials. The systematic relationship included a bias analysis, data extraction and important discussions of the characteristics of the articles selected so that we had breadth of knowledge produced in this theme. Conclusion: We evidenced the need for more research in the area of physical activity and less number of absenteeism due to diseases in workers.